Targeting photodynamic cancer therapy with squaraine cyanine dyes - Lima, Eurico Emanuel Avelar de Serpa Vieira (2024)
The multitude of factors leading to the occurrence of cancer is practically infinite, encompassing causes such as aging, lifestyle, and heredity. Associated with this array of factors is the fact that we are all genetically distinct from one another, which means that no two cancers are alike. This condition limits the existence and discovery of a highly effective therapeutic modality for its treatment. As an alternative to conventional strategies like chemotherapy and radiotherapy, which have limited therapeutic efficacy for some types of cancer and produce various side effects, photodynamic therapy constitutes a promising tool. Photodynamic therapy has existed almost as long as civilization itself. However, despite being forgotten for several centuries, it was revived in the early 19th century as a potentially effective strategy in addressing various current health issues, particularly in the field of oncological diseases. The phototherapeutic effects result from the combination of three individually harmless elements: a photosensitizing molecule, energy in the form of light, and molecular oxygen. Although all three elements play a crucial role, the photosensitizing molecule is the main focus of research by several groups around the world, with thousands of potential photosensitizers of natural, semi-synthetic, or synthetic origin already reported in the literature. Despite being clinically effective, there is a scarcity of photosensitizers that demonstrate the safety and properties inherent to an ideal photosensitizer. Squaraine dyes are a class of polymethine dyes that exhibit properties closely matching several requirements for potential application in photodynamic therapy, notably their absorption at wavelengths where light can penetrate tissues more effectively. Additionally, depending on the structural modifications made to their core, they can reveal other relevant properties such as good stability in aqueous media and under light, as well as the formation of singlet oxygen. Thus, the present thesis aimed to better understand which structural modifications in squaraine dyes allow them to exhibit photophysical, photochemical, and photobiological properties approaching those of an ideal photosensitizer. To this end, throughout the various chapters of this work, several structural modifications to the four-membered central ring were presented: in benz[e]indole derivatives, amines of increasing complexity were introduced and functionalized with groups containing pyridines; and in benzothiazole, indolenine, and benz[e]indole derivatives, γ-aminobutyric acid amino acid, dansylpiperazino group, and a D-(+)-biotin derivative were introduced. For each group of dyes, once fully structurally characterized, photophysical and photochemical studies were conducted to investigate absorption and fluorescence properties, aggregation, light stability, and singlet oxygen formation. The affinity of squaraine dyes for human serum albumin was determined in silico, evaluating their potential as transport vehicles. Additionally, the interaction of biotin-containing dyes with avidin was also assessed. Subsequently, using various tumor cell lines (Caco-2, HeLa, MCF-7, and PC-3) and a non-tumor cell line (NHDF), the photodynamic activity of squaraine dyes was evaluated under non-irradiated and irradiated conditions using LED systems emitting at wavelengths close to the dyes’ maximum absorption. The squaraines showing the most interesting photodynamic effects combined with the most appealing photophysical and photochemical properties were further explored to better understand their mechanism of action. To this end, colocalization studies were conducted to determine in which cellular organelles the dyes accumulate, along with the evaluation of their genotoxic effects, the determination of the reactive oxygen species involved, the mechanism of cell death, and the influence of these dyes on the cell cycle. It was demonstrated that the photodynamic activity of squaraine dyes substantially depends on their structure: the heterocyclic units, the N-alkyl chains, and the functional groups introduced into the squaric ring, with no consistent linearity between a given structural modification and its biological activity. Small structural modifications proved to be the difference between molecules with photodynamic interest and compounds without any therapeutic interest. Thus, this work allowed the identification of highly promising molecules within this therapeutic strategy, which should continue to be studied in the near future. Furthermore, it also elucidated which structural modifications are most advantageous and outlined potential paths to be followed in the synthesis of new squaraine dyes that may exhibit even more pronounced photobiological properties.